ANALISIS KEBIJAKAN HUTANG PADA PERUSAHAAN YANG LISTED DI BURSA EFEK INDONESIA - Beta Asteria (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study is to analyze the effect of liquidity, profitability on debt policy in companies listed on the Indonesia Stock Exchange. Data processing is done by regression analysis using SPSS. The technique used in taking the research sample is purposive sampling. Number of samples that meet the sample criteria are 33 companies. The criteria used are liquid stocks in the 2017 to 2018 research period. The number of samples is 66. Data processing with SPSS shows that partially (t test) it is proven that the variable ability to pay short-term debt (liquidity) affects the company's debt policy while Profitability variable (profitability) is not proven to have an effect on the company's debt policy. Simultaneous Test (F test) proves that the ability to pay short-term debt (liquidity) and profitability (profitability) simultaneously affect the company's debt policy. .